Ice age flood [videorecording (VHS)] : catastrophic transformation of the west - Newman, Jim (Northwest Interpretive Association ; Oregon Public Broadcasting, 1998)
Over 17,000 years ago the landscape of Oregon and Washington changed when glacial dams near Missoula, Montana broke apart and an inland sea of water was released. Tearing through eastern Washington and merging with the Columbia River the flood left what is now the city of Portland under 400 feet of water and carried the fertile soil of eastern Washington to Oregon's Willamette Valley.